Social skills group training in high-functioning autism: a qualitative responder study - Choque-Olsson, Nora; Bölte, Sven (Autism, 2016)
Systematic reviews show some evidence for the efficacy of group-based social skills group training in children and adolescents with autism spectrum disorder, but more rigorous research is needed to endorse generalizability. In addition, little is known about the perspectives of autistic individuals participating in social skills group training. Using a qualitative approach, the objective of this study was to examine experiences and opinions about social skills group training of children and adolescents with higher functioning autism spectrum disorder and their parents following participation in a manualized social skills group training (“KONTAKT”). Within an ongoing randomized controlled clinical trial (NCT01854346) and based on outcome data from the Social Responsiveness Scale, six high responders and five low-to-non-responders to social skills group training and one parent of each child (N = 22) were deep interviewed. Interestingly, both high responders and low-to-non-responders (and their parents) reported improvements in social communication and related skills (e.g. awareness of own difficulties, self-confidence, independence in everyday life) and overall treatment satisfaction, although more positive intervention experiences were expressed by responders. These findings highlight the added value of collecting verbal data in addition to quantitative data in a comprehensive evaluation of social skills group training.